Development and validation of an instrument assessing Health System Responsiveness of family planning services in Sri Lanka - Perera, WLSP; Seneviratne, Rohini; Fernando, Thushara (South East Asia Journal of Public Health, 2013)
Health System Responsiveness (HSR) has been described by the World Health Organization (WHO) as how health systems meet non-medical expectations of its service seekers. It is a multi-domain concept where assessment of responsiveness is made by service seekers. The objective of this study was to develop and validate a Health System Responsiveness Assessment Questionnaire (HESRAQ) in relation to family planning (FP) services in Sri Lanka. Both qualitative and quantitative methodologies were used in the FP delivery settings. Focus group discussions (FGD), in-depth interviews and a modified Delphi method were used. Cross sectional surveys were conducted to carryout exploratory and confirmatory factor analysis (EFA and CFA). Literature reviews, eight FGDs and 45 in-depth interviews were conducted where 15 domains were generated. Eight domains were finalized using a modified Delphi method. A total of ninety two items were generated in the finalized domains. However, 28 items were finalized with expert opinion and EFA with the ratings of 255 respondents. The 28 item instrument was validated with CFA with the rating of 200 respondents, with the six domain model being the most valid (?2=1272, df=335, p<0.000, GFI=0.69) The HESRAQ also showed a high level of reliability for all domains (Cronbach's alpha >0.877). The HESRAQ is a valid and reliable tool to assess HSR of family planning services in Sri Lanka. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13220 South East Asia Journal of Public Health 2011:1:46-52